A Multi-Periodic Optimization Modeling Approach for the Establishment of a Bike Sharing Network: a Case Study of the City of Athens - Saharidis, G KD; Fragkogios, A; Zygouri, E (Lecture notes in engineering and computer science, 2014)
This study introduces a novel mathematical formulation that addresses the strategic design of a bicycle sharing network. The developed pure integer linear program takes into consideration data such as the potential future demand patterns during the day, the bike's popularity in a city, the desired proximity of the stations and the available budget for such a network. With these input data, it optimizes the location of bike stations, the number of their parking slots and the distribution of the bicycle fleet over them in order to meet as much demand as possible and to offer the best service to the users. The estimated demand for the network is split into "Demand for Pick-Ups" and "Demand for Drop-offs" during the 24 hours of the day, which are discretized into time intervals. The proposed approach is implemented on the very center of the city of Athens, Greece.